Study Of Plum Plant Virus Diseases - Marguba Muhammadovna Hamrokulova; Mahfuza Rabbimkizi Muminova (Euro Asian Journal Publishing, 2024)
The article presents an analytical review of the literature sources of diseases affecting plum and measures to combat them. According to the authors, the most common diseases on the plum are: moniliosis, klasterosporiosis, polystigmosis, coccomycosis, powdery mildew. During the autumn examination of plum plantings in the experimental garden of the laboratory "Fruit, berry and ornamental crops", the most severe lesion was noted by polystigmosis, klasterosporiosis and moniliosis
Keywords: plum; disease; polystigmosis; klasterosporiosis